2020
DOI: 10.3390/foods9020173
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Bioactive Metabolites from Pineapple Waste Extracts and Their Antioxidant and α-Glucosidase Inhibitory Activities by 1H NMR

Abstract: Pineapple (Ananas comosus) waste is a promising source of metabolites for therapeutics, functional foods, and cosmeceutical applications. This study strives to characterize the complete metabolite profiles of a variety of MD2 pineapple waste extracts. Metabolomics strategies were utilized to identify bioactive metabolites of this variety prepared with different solvent ratios. Each pineapple waste extract was first screened for total phenolic content, 2,2-diphenyl-1-picrylhydrazyl free radical scavenging, nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…Concurrent treatment with PEAC produced higher activity of CAT in the serum and brain of HFD-fed rats, which indicates the ability of PEAC to scavenge ROS or protect the SOD/CAT system that eliminates superoxide radicals. Extract of pineapple peel have shown presence of phenolic compounds like ferulic acid, gallic acid, epicatechin, catechin, syringic acid [ 33 ]. The protection observed after PEAC treatment of HFD-fed rats suggested a therapeutic impact on HFD-induced metabolic disruption via the normalization of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent treatment with PEAC produced higher activity of CAT in the serum and brain of HFD-fed rats, which indicates the ability of PEAC to scavenge ROS or protect the SOD/CAT system that eliminates superoxide radicals. Extract of pineapple peel have shown presence of phenolic compounds like ferulic acid, gallic acid, epicatechin, catechin, syringic acid [ 33 ]. The protection observed after PEAC treatment of HFD-fed rats suggested a therapeutic impact on HFD-induced metabolic disruption via the normalization of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the solvent extracts of the various parts of A. comosus exhibit antibacterial, antiviral, antifungal, antiparasitic, antiobesity, uterotonic, and anti-inflammatory properties [ [30] , [31] , [32] ]. Fresh pineapple is rich in bromelain, a mixture of different thiol endopeptidases and other components like phosphatase, glucosidase, peroxidase, cellulase, and several protease inhibitors [ 33 ]. The fruit is becoming a favorable fruit in dyslipidemia and obesity with potential in diminishing the severity of cardiovascular syndromes as a result of potent anti-inflammatory bromelain content [ 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the data with regard to the secondary metabolites present in OPL are still considered limited. The peak assignment for signals in the 1D spectra were achieved based on comparisons with literature data [21,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and freely available online databases, including the Nuclear Magnetic Resonance Database (NMRDB) [46], Human Metabolome Database (HMDB) [47], and PubChem [48]. Basically, 3 regions of chemical importance were visually analyzed in the 1 H-NMR spectra of OPL extracts prepared at different extraction solvent, viz., high-field (0.9-3.50 ppm), middle-field (3.50-5.45 ppm) and low-field regions (6.0-8.2 ppm).…”
Section: Visual Inspection Of 1 H-nmr Spectra Of Opl Extracts and Metmentioning
confidence: 99%
“…For these reasons, there is an urgent need to find uses for these food wastes, including fruit peel wastes. Some fruit peels have been recycled into products ranging from agricultural compost, biofuel, and citric acid [3]. However, fruit peels also…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, there is an urgent need to find uses for these food wastes, including fruit peel wastes. Some fruit peels have been recycled into products ranging from agricultural compost, biofuel, and citric acid [ 3 ]. However, fruit peels also provide an excellent source of carbohydrates, fibre, proteins, and phytochemicals, particularly phenolic compounds with high antioxidant capacities [ 4 ].…”
Section: Introductionmentioning
confidence: 99%